2017
DOI: 10.14348/molcells.2017.2307
|View full text |Cite
|
Sign up to set email alerts
|

MAPK3 at the Autism-Linked Human 16p11.2 Locus Influences Precise Synaptic Target Selection at Drosophila Larval Neuromuscular Junctions

Abstract: Proper synaptic function in neural circuits requires precise pairings between correct pre- and post-synaptic partners. Errors in this process may underlie development of neuropsychiatric disorders, such as autism spectrum disorder (ASD). Development of ASD can be influenced by genetic factors, including copy number variations (CNVs). In this study, we focused on a CNV occurring at the 16p11.2 locus in the human genome and investigated potential defects in synaptic connectivity caused by reduced activities of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
(91 reference statements)
1
15
0
Order By: Relevance
“…Among the genes with recurrent mutation and CNV intersection, MAPK3 is particularly interesting with respect to the chromosome 16p11.2 microduplication. Several functional studies on 16p11.2 deletion and duplication mice as well as Drosophila models have suggested that MAPK3 is a key regulator of the syndrome: being downstream of other ASD target genes; involved in axon targeting and regulation of cortical cytoarchitecture; and being the most topologically important gene in the region by PPIs 85-87 . Our analysis builds on these studies by providing evidence of recurrent missense mutation enrichment in human NDDs.…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes with recurrent mutation and CNV intersection, MAPK3 is particularly interesting with respect to the chromosome 16p11.2 microduplication. Several functional studies on 16p11.2 deletion and duplication mice as well as Drosophila models have suggested that MAPK3 is a key regulator of the syndrome: being downstream of other ASD target genes; involved in axon targeting and regulation of cortical cytoarchitecture; and being the most topologically important gene in the region by PPIs 85-87 . Our analysis builds on these studies by providing evidence of recurrent missense mutation enrichment in human NDDs.…”
Section: Discussionmentioning
confidence: 99%
“…This CNV is associated with a variable phenotype, in terms of the clinical profile and degree of symptom severity [Golzio & Katsanis, ; D'angelo et al, ; Snyder et al, ; Steinman et al, ]. The 16p11.2 chromosomal region spans approximately 29 genes, including MAPK3 and MVP —both potentially influencing synaptic function and cortical plasticity [Park, Park, & Lee, ]. The loss (DEL) or gain (DUP) of these ~29 genes in the 16p11.2 has a population prevalence of ~0.05% for DEL and ~0.04% for DUP [Kirov et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the protein encoded by MAPK7 is a member of the MAPK family involved in a wide variety of cellular processes, such as proliferation, differentiation, transcription regulation, and brain development (Pearson et al 2001), and abnormalities in these processes can lead to the development of ASD symptoms (Nagy et al 2017;Courchesne et al 2019). Previous evidence also indicated rare mutations in the MAPK gene family participating in ASD, such as MAPK3 (Park et al 2017) and MAPK1 knockout mice showing ASD-like behavior (Satoh et al 2011). Together with these results of de novo SNVs in MAPK7, it may be inferred from this study that mutations in the MAPK family may involve the genes that affect multiple cellular processes, resulting in the inability of cells to develop and mature normally, leading to the onset of ASD.…”
Section: Discussionmentioning
confidence: 99%